The Role of Job Stress to Work – Life Balance among Women Nursing Paramedic at Medan City Hospital - Putri Fatimah; Surnarsih -; Alfina Tiurmida Sitanggang; Arifin -; Raspan - (Psikologi Prima, 2024)
The research examines the role of job stress in work-life balance among women nursing paramedics at Medan City Hospital. This research used a quantitative method. A total of 324 women nursing paramedics at Medan City Hospital participated in this research. The measurement was conducted using the job stress and work-life balance scales. Data on this research was analyzed using a linear regression test. The results of this research show a role of job stress and work-life balance among female nursing paramedics because the statistic shows that T value -8.8260  > T table 1.960 and p = 0,000 < 0,050. Another result is that the job stress of women nursing paramedics is categorized as high, and the work-life balance of women nursing paramedics is categorized as low. Therefore, it is recommended that further research be carried out with qualitative methods or mixed design and consider other variables.